Case report: Heart retransplant from a donor after circulatory death and extended transport period with normothermic perfusion - Kasinpila, Patpilai; Ruaengsri, Chawannuch; Koyano, Tiffany; Shudo, Yasuhiro (Frontiers in Cardiovascular Medicine, 2023)
A 55-year-old man with end-stage heart failure, who had an orthotopic heart transplant 21 years prior, underwent heart retransplantation using a heart from a donor with circulatory death in a distant location and an extended transport period with normothermic ex vivo perfusion. Owing to the persistent and worsening shortage of donor hearts, this case illustrates that expanding the donor acceptance criteria to include more distant donor locations and enrolling recipients with extended criteria (e.g., heart retransplantation) is feasible.